Study of interdisciplinarity in chemistry research based on the production of Puerto Rican scientists 1992-2001. Interdisciplinarity, Bibliometric indicators, Chemistry - Elias Sanz-Casado; Carmen Martin-Moreno; Carlos Garcia-Zorita; Maria Luisa Lascurain-Sanchez (Information Research: An International Electronic Journal)
Determining the role played by interdisciplinarity in the generation of knowledge is a very fertile line of research in which synergies among different fields of science can be identified and their impact on research efficiency ascertained. A number of methods may be used to explore interdisciplinarity, from the sociological approach to those requiring the application of bibliometric indicators. In this paper, a bibliometric analysis of the research conducted by scientists with the Chemistry Department at the University of Puerto Rico was run on the basis of the subject matter of citing and cited papers, in order to ascertain how interdisciplinarity affects certain aspects of research, such as collaboration or visibility. The data used for this paper were taken from the Science Citation Index database, which lists the most significant contributions made by these scientists, along with the respective bibliographic references. The study revealed the existence of scientific areas that are highly dependent on the knowledge generated in the specific area itself. A positive, albeit weak, correlation was also observed between research interdisciplinarity and collaboration between researchers and institutions. Interdisciplinarity was not found to have any effect, however, on the visibility of research papers or to be correlated with international collaboration.